2016
DOI: 10.1021/acsami.6b09541
|View full text |Cite
|
Sign up to set email alerts
|

Diverging Effects of Topographical Continuity on the Wettability of a Rough Surface

Abstract: The effects of the continuity of the surface pattern on wetting enhancement was investigated using micropillar and microhole arrays on hydrophilic and hydrophobic materials. Isolated micropillar arrays and continuous microhole arrays were prepared by a microscale imprinting technique using positive and negative Si molds fabricated by a conventional photolithography technique. The contact angles (CAs) and contact angle hysteresis (CAH) of the prepared surfaces were measured as a function of the surface paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…This method differs from typical vibrational resonance techniques that seek maximum harvesting outcomes at resonant frequencies from vibrational mechanical sources in a broad range of frequency. [ 26–29 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This method differs from typical vibrational resonance techniques that seek maximum harvesting outcomes at resonant frequencies from vibrational mechanical sources in a broad range of frequency. [ 26–29 ]…”
Section: Resultsmentioning
confidence: 99%
“…For ceramic‐based piezoelectric generators, most of the reported harvesting results are based on cantilever‐type harvesters using vibrational mechanical sources over a wide range of frequencies (reaching a few hundred hertz). [ 26–28 ] The maximum harvesting performance is achieved at a specific resonant frequency (typically ranging from ≈40 to 500 Hz). This resonant frequency is determined by factors, such as the choice of piezoelectric material, device structure, vibrational source, and measurement condition.…”
Section: Introductionmentioning
confidence: 99%
“…They have shown that the anisotropy can be controlled by the height of the pillars and is only observed for hydrophilic surfaces. In practice, surface patterning can be achieved by various methods such as microcontact printing, photolithography, , and vapor or cold spray surface deposition. , Other recent practical patterning techniques such as microplasma jets, electrochemical etching, and using nanometer-scale particles have shown great potential in creating surfaces with desired wetting properties. Anisotropic wettability has attracted much interest due to its importance in developing microfluidic devices, molecular separation and sensing, and self-cleaning surfaces .…”
Section: Introductionmentioning
confidence: 99%
“…Anisotropic wettability has attracted much interest due to its importance in developing microfluidic devices, molecular separation and sensing, and self-cleaning surfaces . It provides a mechanism for the directional control of liquid flow by restricting the movement of droplets in specific directions. The existing research on anisotropic wettability has focused on macroscale water droplets. However, no studies have considered anisotropic wettability at the nanoscale for alkanes.…”
Section: Introductionmentioning
confidence: 99%
“…The entrapped air hinders the spreading dynamics and wetting transition inside the isolated microcavity. [ 35,36 ] Following the omniphobic and superomniphobic microtextures composed of reentrant and doubly reentrant pillars, [ 37–39 ] Domingues et al. [ 40,41 ] designed a landmark omniphobic surfaces with doubly reentrant cavities that can significantly improve the stability of the air–liquid interface and achieve robust entrapment of air upon immersion in wetting liquids.…”
Section: Introductionmentioning
confidence: 99%